Scaling rules for high quality soliton self-compression in hollow-core fibers - Schade, Daniel; Köttig, Felix; Koehler, Johannes R.; Frosz, Michael H.; Russell, Philip St. John; Tani, Francesco (Optics Express, 2021)
Soliton dynamics can be used to temporally compress laser pulses to few fs durations in many different spectral regions. Here we study analytically, numerically and experimentally the scaling of soliton dynamics in noble gas-filled hollow-core fibers. We identify an optimal parameter region, taking account of higher-order dispersion, photoionization, self-focusing, and modulational instability. Although for single-shots the effects of photoionization can be reduced by using lighter noble gases, they become increasingly important as the repetition rate rises. For the same optical nonlinearity, the higher pressure and longer diffusion times of the lighter gases can considerably enhance the long-term effects of ionization, as a result of pulse-by-pulse buildup of refractive index changes. To illustrate the counter-intuitive nature of these predictions, we compressed 250 fs pulses at 1030 nm in an 80-cm-long hollow-core photonic crystal fiber (core radius 15 µm) to ∼5 fs duration in argon and neon, and found that, although neon performed better at a repetition rate of 1 MHz, stable compression in argon was still possible up to 10 MHz.
CRIS-Team Scopus Importer:2021-06-18